The Reproductive Biology of the Surf Clams Triangle Shell (Spisula aequilatera), Ringed Dosinia (Dosinia anus) and Deep Water Tuatua (Paphies donacina) from the North-East of South Island, New Zealand - Aljadani, Nuha (Auckland University of Technology, 2013)
Surf clam is an important marine organism which plays vital roles in terms of commercial and ecological roles. Commercial harvesting of them is well established at an international level although still the industry use of them is limited in NZ. To sustainably increase surf clam harvesting at a commercial level, the authorities seek to enhance basic researches, particularly around the reproductive biology of clam species. Thus, throughout this study, the aim is to investigate the gametogenesis and gonadal development of Paphies donacina, Dosinia anus and Spisula aequilatera which the species are economically important in Cloudy Bay environment. To investigate the reproductive biology of the three species, this study employs two different methodologies which are histological techniques and develop a condition index. The study examines samples extracted from Cloudy Bay from Aug, 2012 to Jul, 2013 for each month to determine the seasonal variations in the reproductive biology of the three species. The study uses statistical techniques extensively to generalize the findings from the samples into the Cloudy Bay populations. From the above techniques, the current study has found that there are significant seasonal variations in varying extents in the reproductive cycles of the three species. The findings further have concluded that histological techniques are the most appropriate way to investigate the gametogenesis and gonadal development of surf clams over the condition index. It has been clear that temperature is an important exogenous factor that determines reproductive behaviours of Paphies donacina, Dosinia anus and Spisula aequilatera in Cloudy Bay. In addition, this study provides directions for future studies to extend the knowledge discovered from this research. It is hoped that these findings could minimize the research gaps bound around surf clam investigations in NZ context.
Keywords: Surf clams; New Zealand